Temperature Dependence of the Concentration Kinetics of Absorption of Phosphate and Potassium in Corn Roots - Bravo-F, Pedro (1981)
The effect of temperature on respiration and kinetics of H(2)PO(4)(−) and K(+) uptake in corn roots was determined in the range of 2 to 42 C. The response of uptake to temperature, determined from Q(10) and activation energy (Ea) data, for the anion and the cation differ significantly, especially in the range of uptake mechanism (Mech.) I. At 2.5 micromolar the Ea for K(+) uptake below the 13 C transition is 29.3 kilocalories per mole. As the K(+) concentration is increased, Ea declines and at 0.25 millimolar is 21.6 kilocalories per mole. Accompanying this change in Ea is a shifting of the apparent transition temperature from 13 to 17 C. Above the temperature transition the Ea's for K(+) uptake in the Mech. I range are quite low (3.0) and this value is unchanged by increases of K(+) concentration to 0.25 millimolar. In the range of Mech. II above 1 millimolar K(+) the temperature transitions are not seen and plots become linear. The Ea's show an increasing trend from 4.7 at 1 millimolar to 6.1 at 50 millimolar. The uptake of H(2)PO(4)(−) is much more temperature sensitive having a constant Ea at concentrations in the Mech. I range below the 13 C temperature transition. The Arrhenius plots reveal a second transition at 22 C and the Ea for this segment is 21.0. Above the second transition the Ea remains high (10.0) and is constant in the range of Mech. I. In the range of Mech. II there is a concentration dependent decline in Ea for H(2)PO(4)(−) uptake (22.7 at 1.0 millimolar to 1.0 at 50 millimolar). There is no definable low temperature transition at these concentrations. Ion uptake is found to be much more sensitive to low temperature than respiration in this chill-sensitive species. The data suggest that the low temperature reduction of ion transport is more closely related to restriction of function of active transport systems than to either respiration or membrane permeability.